Study of infrared excess from circumstellar disks in binaries with Spitzer/IRAC. (30th July 2015) - Itoh, Yusuke; Fukagawa, Misato; Shibai, Hiroshi; Sumi, Takahiro; Yamamoto, Kodai
Abstract : The presence of excess emission in the 3.6–8.0 μm region was investigated in a sample of 27 binary star systems located in two nearby star-forming regions, Taurus and Ophiuchus, by using Spitzer/Infrared Array Camera (IRAC) archival data. Angular (Projected) separations of the binaries are greater than 2″ (∼ 280 au), which enables us to perform spatially resolved photometry of individual primary and secondary sources. The measured occurrence of infrared excess suggests that binarity plays a role in the evolution of circumstellar disks, even at such wide binary separations. Most of the binaries have excess emission from both the circumprimary and circumsecondary disks, or show photospheric levels for both components at all four wavelengths of IRAC. On the other hand, four binary systems ($17^{+11}_{-8}$ %, designated by "mixed" systems) exhibit the excess emission from a single binary component. This ratio is significantly smaller than that predicted by the random pairing of single stars, suggesting that circumprimary and circumsecondary disks are synchronously dispersed. In addition, the excess frequencies (EFs) of primary and secondary sources with a projected distance of a p ≃ 280–450 au are $100^{+0}_{-17}$ % and $91^{+8}_{-18}$ %, respectively, and significantly higher than that of single stars (70% ± 5%). We made a simple model describing the EF distribution as a function of the disk outer radius, R out . Comparisons with observations using the Kolmogorov–Smirnov test show that the observational data are consistent with the model when the EF ≃ 100% region is found at R out  ∼ 30–100 au. This disk radius is smaller than that typically estimated for single stars. The high EF of circumstellar disks with these radii may indicate a prolonged lifetime of dust in binary systems, possibly because the smaller disks counteract mass loss by photoevaporation.